Enhancing Early Childhood Health Through Clean and Healthy Living Behavior (PHBS) Education Using the Drill Method In The Rubiq Program: Peningkatan Kesehatan Anak Usia Dini Melalui Edukasi Perilaku Hidup Bersih Dan Sehat (PHBS) Dengan Metode Drill Di Program Rubiq (JURNAL UNEJ, 2024)
The program called Rumah Belajar Asiq (RUBIQ) aims to improve the health of young children through education on Clean and Healthy Living Behavior (PHBS) using the drill method. This activity was carried out by the KKN 241 University of Jember Group at RA Al-Hikmah and PAUD Bendera Bangsa. The drill method is applied to teach practical skills, such as washing hands and brushing teeth properly. The results of this activity showed significant improvements in children's understanding and skills, with an average score increase of 30% for washing hands and 40% for brushing teeth. The drill method has proven to be effective in increasing children's knowledge and skills and forming healthy habits from an early age, which contributes to improving the quality of public health.